DESIGNING A ROUTER REDUCTION SYSTEM USING HOT STANDBY ROUTER PROTOCOL METHOD FOR BACKUP LINK IN DITJEN PPKL - Andri Nuki Baskoro; Anton Anton; Puji Astuti (Jurnal Techno Nusa Mandiri, 2020)
Computer networks play an important role in data communication at companies or government institutions to support them in terms of work. In this case, the authors conducted observational research and direct interviews with IT staff at the Ditjen PPKL Control about how the network operates in that place. Routers have a very important role in data communication and connecting different networks, so a router reduction system is needed as a solution to minimize failures on the network or these devices. The network topology in each office or government agency is different, which makes the problems in each government office or agency different. Based on the research that has been done, the network of the Ditjen PPKL often experiences a link down which causes disconnection of the internet connection and hinders the productivity of staff. So a router redundancy system is needed to maintain network availability, such as the Hot Standby Router Protocol (HSRP) which has two lines, one as the mainline and the other as a backup if the mainline is down. That way network availability will always be maintained without having to wait for the IT staff to do troubleshooting if there is a network failure. The result of this research is to provide maintained network availability. Even if a link goes down, the network will automatically return to normal.